Acoustic wave radiation from a coaxial pipe with partial lining and inner perforated screen - TİRYAKİOĞLU, BURHAN (My University, 2023)
In this study, the analysis of sound waves from a coaxial pipe with a perforated screen and a partial acoustic absorbing lining is investigated. The geometry under consideration consists of an infinite pipe placed in a semi-infinite cylindrical pipe such that the inner surface of the outer pipe is covered with a partial acoustic absorbing lining. Because of the partial lining, the solution is obtained with both the Jones’ method and the Mode-Matching method. The effects of the problem parameters such as perforated screen and partial lining on the radiation phenomenon are presented.
Keywords: Havacılık ve Uzay Mühendisliği; Fizik; Elektromanyetizma, Akustik, Isı Transferi, Klasik Mekanik ve Akışkanlar Dinamiği; Akustik; Temel Bilimler; Mühendislik ve Teknoloji; Aeronautical and Space Engineering; Physics; Electromagnetism, Acoustics, Heat Transfer, Classical Mechanics and Fluid Dynamics; Acoustics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; AKUSTİK; MÜHENDİSLİK, HAVACILIK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; PHYSICS; ACOUSTICS; ENGINEERING, AEROSPACE; Uzay Mühendisliği; Fizik Bilimleri; Akustik ve Ultrasonik; Aerospace Engineering; Physical Sciences; Acoustics and Ultrasonics; acoustic lining; coaxial pipe; mode-matching; perforated screen; Wiener–Hopf